Factors associated with the practice of early complementary feeding and its impact on the nutritional status of infants aged 7 to 23 months - Rika Nurhasanah; Achmad Fauzi; Indria Astuti (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Proper complementary feeding plays a crucial role in influencing an infant's nutritional status. Key factors to consider when introducing complementary foods include the starting age, the consistency and texture of the food, the portion size, and the frequency of feeding. Purpose: To identify factors related to the practice of early complementary feeding and their impact on the nutritional status of infants aged 7 to 23 months. Method: A quantitative analytical research with a cross sectional design. Respondent were selected using purposive sampling and the Slovin formula, resulting in 51 respondent from Sipayung Village. Univariate statistical analysis was conducted, including chi square test. Results: The chi-square test revealed a significant relationship between nutritional status and factors such as the age of feeding onset (p=0.015), consistency of delivery (p=0.006), portion size (p=0.000), and feeding frequency (p=0.000). In the "good nutrition" category, the majority were in alignment with the recommended feeding guidelines: 41 (87.2%) for age of onset, 40 (88.9%) for consistency of delivery, 40 (90.0%) for portion size, and 41 (91.1%) for feeding frequency. On the other hand, malnutrition was more common in those not following the appropriate guidelines: 3 (75.0%) for age of onset, 4 (66.7%) for consistency of delivery, 5 (71.4%) for portion size, and 5 (83.3%) for feeding frequency. Conclusion: A significant relationship exists between the practice of providing complementary breastfeeding and factors such as the age of onset of feeding, consistency of delivery, quantity of food, and feeding frequency.